Low Profile, Dual-Polarised Antenna for Aeronautical and Land Mobile Satcom - Martin Shelley; Robert Pearson; Javier Vazquez (International Journal of Antennas and Propagation)
High data rate communications on the move is fastly becoming a major application area for satellite systems using Ku- and higher frequency bands. The ground terminal antenna used in such systems has a profound impact on the system capabilities and is constrained in many often conflicting ways. While simple reflector systems offer the lowest cost solution, there is a widespread need for low profile antennas to minimize the antenna visual signature and to satisfy aesthetic and transportation requirements. It is often considered that the use of such antennas will compromise the system performance.